Saccharomyces cerevisiae exposed to titanium dioxide nanoparticles of less than 100 nm in size under heat shock partially reverted glucose-mediated repression of the citrate cycle - Capela-Pires, J (2018)
Energy metabolism in yeast cells can be manipulated by providing different carbon sources: Saccharomyces cerevisiae grown on glucose rapidly proliferates by means of fermentation, whereas in non-fermentable carbon sources, such as glycerol, metabolism shifts towards respiration. In general, fermentation is preferred by the yeast in rapidly proliferating cells even in the presence of oxygen, a process also called the Crabtree effect. In the present study, it was observed that the addition of glucose to S. cerevisiae UE-ME3 grown in a glycerol-rich medium caused an increase in the growth-marker enzyme alkaline phosphatase and a blockage of respiratory enzymes. In addition, the simultaneous exposure of yeast cells to TiO2-NP <100 nm (5 μg/mL) under heat shock (28/40), after 100 min of culture in respiratory-fermentative mode, caused a partial reversion of glucose-mediated repression of citrate synthase and succinate dehydrogenase activities, key-enzymes of the citrate cycle, and a decrease in the level of alkaline phosphatase activity similar to those detected in cells grown in respiratory mode.